Changing of the broadcasting rights in connection with the Winter Olympic Game in Sochi - Várhegyi , Ferenc; András , Krisztina (Applied Studies in Agribusiness and Commerce, 2015)
The authors examine how the broadcasting rights have changed relating to the International Olympic Committee’s (IOC) changed media politics in the case of to the Winter Olympic Games in 2014. They present the market of the broadcasting rights and the changing of the incomes of the media rights fees. They are also examining the target of the IOC relating to the television market and exploring how it might impact the life of the broadcasting and public service media.